Competence induction of homologous recombination genes protects pneumococcal cells from genotoxic stress - David De Lemos; Anne-Lise Soulet; Violette Morales; Mathieu Berge; Patrice Polard; Calum Johnston (mBio)
ABSTRACT Homologous recombination (HR) is a universally conserved mechanism of DNA strand exchange between homologous sequences, driven in bacteria by the RecA recombinase. HR is key for the maintenance of bacterial genomes via replication fork restart and DNA repair, as well as for their plasticity via the widespread mechanism of natural transformation. Transformation involves the capture and internalization of exogenous DNA in the form of single strands, followed by HR-mediated chromosomal integration. In the human pathogen Streptococcus pneumoniae, transformation occurs during a transient, stress-induced differentiation state called competence. RecA and its partner DNA branch migration translocase RadA are both well conserved and cooperate in HR during transformation and certain genome maintenance pathways. Both recA and radA genes are basally expressed and transcriptionally induced during competence. In this study, we explored the importance of competence induction of recA and radA in transformation and genome maintenance. We confirmed that competence induction of recA, but not radA, was important for transformation. In contrast, we uncovered that the competence induction of both genes was required for optimal tolerance faced with transient exposure to the lethal genotoxic agent methyl methanesulfonate. However, this was not the case for another DNA-damaging agent, norfloxacin. These results show that competence induction of HR effectors is important for the increased tolerance to genotoxic stress provided to competent pneumococci. This reinforces the finding that pneumococcal competence is a stress-sensing mechanism, transiently increasing the expression of some genes not to optimize transformation but to improve survival faced with specific lethal stresses.IMPORTANCEHomologous recombination (HR) is a mechanism of DNA strand exchange important for both the maintenance and plasticity of bacterial genomes. Bacterial HR is driven by the recombinase RecA along with many accessory partner proteins, which define multiple dedicated pathways crucial to genome biology. Thus, a main mechanism of genome plasticity in bacteria is natural genetic transformation, which involves uptake and chromosomal integration of exogenous DNA via HR. In the human pathogen Streptococcus pneumoniae, transformation occurs during a transient, stress-induced physiological state called competence. RecA and the helicase RadA are key for both genome maintenance and transformation, and both are over-produced during competence. Here, we explore the importance of this over-production for transformation and genome maintenance, quantified by tolerance to genotoxic stress. While over-production of RecA was important for both processes, over-production of RadA was required only for genotoxic stress tolerance. This highlights the importance of competence as a stress-responsive mechanism, with induction of HR genes important for genotoxic stress tolerance.